The Snowden files : the inside story of the world's most wanted man - Harding, Luke (London : Guardian Books, 2014)
Edward Snowden was a 29-year-old computer genius working for the National Security Agency when he shocked the world by exposing the near-universal mass surveillance programs of the United States government. His whistleblowing has shaken the leaders of nations worldwide, and generated a passionate public debate on the dangers of global monitoring and the threat to individual privacy. In a tour de force of investigative journalism that reads like a spy novel, award-winning Guardian reporter Luke Harding tells Snowden's astonishing story--from the day he left his glamorous girlfriend in Honolulu carrying a hard drive full of secrets, to the weeks of his secret-spilling in Hong Kong, to his battle for asylum and his exile in Moscow. For the first time, Harding brings together the many sources and strands of the story--touching on everything from concerns about domestic spying to the complicity of the tech sector--while also placing us in the room with Edward Snowden himself. The result is a gripping insider narrative--and a necessary and timely account of what is at stake for all of us in the new digital age"-- Provided by publisher.
Includes index.
Keywords: Snowden, Edward J; Whistle blowing -- United States; Leaks (Disclosure of information) -- United States; United States. National Security Agency